Urinary carcinogenic 4–6 ring polycyclic aromatic hydrocarbons in coke oven workers and in subjects belonging to the general population: Role of occupational and environmental exposure - Campo, Laura; Fustinoni, Silvia; Consonni, Dario; Pavanello, Sofia; Kapka, Lucyna; Siwinska, Ewa; Mielzyňska, Danuta; Bertazzi, PierAlberto (International journal of hygiene and environmental health, 2014)
A new solid phase microextraction–gas chromatography–mass spectrometry method (SPME–GC–MS) to detect urinary unmetabolized 3-, 6-ring polycyclic aromatic hydrocarbons (PAHs) was applied to coke oven workers and general population subjects with the aim to assess exposure to carcinogenic PAHs, to evaluate the role of occupational and environmental variables on PAHs levels, and to compare present results with those previously obtained with a less sensitive method. A total of 104 coke oven workers (CW) from Poland [recruited in 2000 (CW-2000; n=55) and 2006 (CW-2006; n=49)], and 45 control subjects from the same area, provided urine spot samples for measurement of 10 PAHs (from phenanthrene to benzo[g,h,i]perylene). The comparison between the two methods was performed only on CW-2000 subjects. Information regarding personal characteristics and job variables was collected by a questionnaire. The new method enables the quantification of 5-, 6-ring PAHs; precision and accuracy were in the 7.3–20.8% and 89.4–110% range, respectively; in CW-2000 samples results obtained with the new and the old method were highly correlated (Lin's concordance correlation coefficients: from 0.790 to 0.965); the mean difference between measured PAHS increased with the molecular weight of the analytes (from +5 to +27%). Urinary PAHs were above or equal to the quantification limit, depending on the compound, in 67–100% (min–max), 26–100% and 6–100% of samples from CW-2000, CW-2006 and controls, respectively. Chrysene and benz[a]anthracene were the most abundant carcinogenic PAHs with median levels of 43.4, 13.4, and 2.3ng/L and 45.9, 14.9, and 0.7ng/L in CW-2000, CW-2006, and controls, respectively, while benzo[a]pyrene levels were 6.5, 0.7 and <0.5ng/L. The multiple linear regression model showed that the determinants of exposure were the use of wood and/or coke for house heating for controls, and job title or the plant for CW-2006. Urinary benzo[a]pyrene and other carcinogenic PAHs were, for the first time, quantified in urine samples from both occupationally and environmentally exposed subjects. These results show that urinary PAHs can discriminate exposure at different levels. Moreover, the simultaneous determination of several PAHs allows for the development of excretion profiles to assess exposure to specific compounds.